BORU NI RAJA HATOBAN - Tinjauan Filsafat Anthropologis atas Kaum Perempuan di dalam Budaya Batak Toba - Simamora, Serpulus T. (Universitas Katolik Santo Thomas Sumatera Utara, 2002)
One of many definitions offered to explain human existence is that human being is a paradoxal being. By paradoxical being one intends that the very existence of human being is perceived in its seemingly contradictory expression without being contradiction. Human being is material-spiritual, individual-social, etc. This paradoxical nature constitutes human existence. It affects essentially his/her personality, religion, act, culture, etc. Social status of women in Toba Batak culture is placed in such paradoxical situation too. In one hand, they are invoked as âBoru ni Rajaâ (the honored daughter), but on the other hand, they are treated as âhatobanâ (slaves). This article seeks to show critically the place of Toba Batak women in Toba Batak culture. Our purpose, therefore, is to present the social status of Toba Batak women inherited culturally from ancestors. By critically we mean that we seek to present fairly the social status of women in both its negative side and positive one.